Consumerism: where does Consumer See Himself? - Sadar, S. B.; Fulzele, T. U. (Indian Journal of Marketing, 2005)
The Indian Consumers gained focus, only after disgruntled consumers started reaching and voicing their grievances against unscrupulous traders and manufacturers of goods and service. Government of India has accorded high priority for consumer protection. The legislative measures in India cover various aspects of consumer protection since 1930 up to the enactment of Consumer Protection Act, 1986. Consumerism is a national problem afflicting every section of the society, men and women whether old, youth or child, rich or poor, rural or urban, literate or illiterate. Consumer protection is a form of social action, which is designed to attain the well being of one group within a society namely the consumers.